Hidrogel no plantio de mudas de Eremanthus erythropappus (DC.) MacLeish - Pinto Júnior, José Alvim (2016)
Due the recurrent need of new information about agricultural and forest production, mainly in coasts downshifts and productivity increase, new technologies integrating natural resources are emerging, aiming to optimize the hydric consume during the plantation. Among a lot of technologies, hydrogel (known as a hydric polymer, holding the characteristic to regulate water availability in plantations and decreasing the irrigation frequencies) usage stands out. This study’s aim was to verify the potential usage of hydrogel during the establishment of Eremanthus erythropappus seedling in field and menage experiments. Three hydrogel commercial brands were used (G1, G2 and G3), and the experiment was performed in a greenhouse in Forestry nursery of UFLA. A completely randomized design in factorial project 3 x 5 was performed between April and July 2015, with and without irrigation, or using pure water or water solution with gel to irrigation. High (H), diameter (DC), daily evapotranspiration (ET), the permanent wilting point, aerial (MSPA) and root (MSR) part of the plant dry content were determined at the end of the experiment. Field experiments were performed in Aiuruoca, Minas Gerais state, utilizing a experimental delineation with casual blocks in factorial project 3 x 5, with four repetitions, where each plot had nine plants. Three hydrogel brands were used, with five different doses of the polymer (0,0; 0,5; 1,0; 1,5; 2,0 kg/400 L water) and survival, high a seedling diameter were evaluated. Evaluations were performed in 15, 25, 40 and 55 days (in greenhouse) and 25, 50, 95, 140, 200 and 260 days (field experiment) after plantation. G1 and G3 seedlings in the greenhouse presented bigger diameter and high, and we do not indicated it’s usage with irrigation gel. G1 and G3 also were the ones who endured the biggest period to PMP. In field experiment, G1 seedlings had the best survival rates in 50 and 260 days after plantation, and bigger H and DC. During the hydric deficit period, there was an increase in diameter in the seedlings due the augmentation of the doses used.